17 Standard ultrastaging (SU) compared to one-step nucleic acid amplification (OSNA) for sentinel lymph nodemetastasis detection in endometrial cancer patients: a retrospective large cohort comparison. (18th September 2019) - Buda, A; Fanfani, F; Monterossi, G; Vecchione, F; La Fera, E; Adorni, M; Vicini, D; Gioé, A; Di Martino, G; De Ponti, E; Zannoni, GF; Perego, P; et al.
Abstract : Objectives: We compared the traditional ultrastaging (SU) with the one-step nucleic acid amplification (OSNA) for the detection of sentinel lymph node (SLN) metastasis in women with apparent early stage endometrial carcinoma (EC). Methods: All women were surgically staged including SLN mapping. Nodes were cut perpendicular to the long axis and two adjacent 5 mm sections were cut at each of 2 levels 50 mm apart, and one slide was stained with H&E and the other with immunohistochemistry using the AE1/AE3 anticytokeratin antibody, and one negative control slide for a total of five slides per block. For OSNA analysis, the 2mm sections of the SLN were homogenized to form a lysate that was centrifuged and inserted into the RD100i instrument where for the isothermal amplification of CK19 mRNA. Results: Totally 409 patients were included in the analysis (183 OSNA, 226 SU). Overall, 3521 lymph nodes were removed, of those 871 SLN's (24.7%) were identified (381 OSNA, 490 SU). Sixty patients had metastasis on SLN's (26 OSNA, 34 SU). Macrometastasis, micrometastases, and ITC were 25.7%, 68.6% and 5.7% for OSNA; 48.1%, 36.5% and 15.4% for SU (p = 0.015). ITC alone were recorded in 7 women (2 OSNA, 5 SU). Conclusions: The OSNA assay detected a higher rate of micrometastasis and a lower rate macrometastasis and ITC compared to SU. The clinical and prognostic impact of ITC is still controversial. Further studies are needed to clarify the clinical impact of the OSNA assessment technique and the prognostic impact of ITC in patients with stage I EC.